2018
DOI: 10.1123/pes.2017-0058
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Spatiotemporal Variables and Ground Reaction Forces During Sprinting in Boys

Abstract: There was a stage of temporal slower development of sprinting ability from age 8.8 to 12.1 years, being characterized by unchanged propulsive force and decreased step frequency. Moreover, increasing propulsive forces during the middle acceleration and maximal speed phases and during the initial acceleration phase are probably responsible for the rapid development of sprinting ability before and after the period of temporal slower development of sprinting ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 22 publications
5
32
1
Order By: Relevance
“…The mechanisms behind such adaptations could include the previously observed age-related increases in musculotendon unit stiffness 31 and enhanced stretch reflex 32 in children. The finding of increased propulsive impulse, which may be augmented by the aforementioned enhanced stretch-shortening ability, mirrors that of previous studies 5,7 where this was associated with age-related sprint performance enhancements due to increased step length.…”
Section: F I G U R Esupporting
confidence: 87%
See 3 more Smart Citations
“…The mechanisms behind such adaptations could include the previously observed age-related increases in musculotendon unit stiffness 31 and enhanced stretch reflex 32 in children. The finding of increased propulsive impulse, which may be augmented by the aforementioned enhanced stretch-shortening ability, mirrors that of previous studies 5,7 where this was associated with age-related sprint performance enhancements due to increased step length.…”
Section: F I G U R Esupporting
confidence: 87%
“…Additionally, these were associated with improvements in antero-posterior force production allowing more effective reversal of the braking phase to more rapidly generate higher propulsive impulse. Collectively, previous research has revealed two general periods of rapid development (from ages 5-8 years and age 11/12 onwards, the latter occurring around PHV) using both cross-sectional 1,[5][6][7]21 and longitudinal study designs. [2][3][4]22 Given the limited age ranges of participants in this study and due to the fact that girls on average mature earlier than boys, only one of these periods of rapid development was captured for each sex in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes may also contribute to the preferential utilization of stretch-shortening cycle and development of hypertrophy and force power velocity characteristics of the plantarflexor muscles, because eccentric loads allow the generation of more muscle force, power and velocity than isolated concentric actions (Lieberman, 2012). This suggests that even though an acute decrement in performance occurs when sprinting barefoot, the utilization of some barefoot sprinting may help children develop the ability to engage the plantarflexor muscles during the rapid stretch-shortening cycles that may result in an increase in the ground reaction forces during the stance phase of sprinting (Nagahara et al, 2018;Rossi et PeerJ reviewing PDF | (2018:02:25444:1:1:NEW 31 May 2018)…”
Section: Discussionmentioning
confidence: 99%